Iatrogenic Hip Instability After Hip Arthroscopy: Is There a Role for Open Capsular Reconstruction?. Issue 2 (April 2019) - Gehrman, Max; Cornell, Max; Seeley, Mark
Abstract : Case: A 23-year-old female athlete presented with postoperative hip pain and laxity following 3 arthroscopic hip procedures. Conclusions: Open reconstruction of the anterior hip capsule with Achilles allograft can correct arthroscopy-induced hip laxity.